STUDI PERBANDINGAN EFEKTIVITAS MATERIAL BAMBU DAN BATU BATA SEBAGAI KONSTRUKSI DINDING - Lilis Trianingsih, Retna Hidayah (Universitas Negeri Yogyakarta, 2014)
This paper aims to examine the effectiveness of bamboo and bricks, by conducting a comparative literature study of the two materials. The method used in the writing of this paper is to conduct a literature review related to bamboo and bricks as wall construction. There are 7 indicators were used as a comparative aspect to measure the level of effectiveness, include of: sustainability, nature of physical and mechanical properties, safety against earthquakes, thermal comfort, cost of construction, and durability. The result indicates the effectiveness comparison of bamboo and bricks.Keywords: sustainable building materials, wall consrtruction, bamboo, bricks